Seismic vulnerability, risk assessment, mitigation, response and recovery activity in a low risk state: Pennsylvania's experience - Fischer, Henry W. III; Geiger, Charles J.; Scharnberger, Charles K. (1999)
The Commonwealth of Pennsylvania, like many states in the USA, is found to be a low-risk area in terms of seismic vulnerability. Like many other states, however, it is vulnerable to future episodes which could be quite threatening to a sizeable population. Degree of seismic vulnerability varies across the commonwealth. Pursuant to assessing Pennsylvania's earthquake preparedness, the commonwealth's 67 local emergency management agency (LEMA) coordinators were asked to complete a mail-questionnaire which sought to determine their degree of earthquake (EQ) experience, risk assessment activity, mitigation activity, and planning for response and recovery. A response rate of 87% was attained. The experience, activity, and planning levels were found to be consistently low regardless of the seismic vulnerability level of the county. These findings are consistent with research literature which describes the circumstances under which hazard reduction is likely to occur. Public administrators in other states might benefit from conducting their own risk assessment, as well as assessing their own mitigation activity and planning for response and recovery - as the findings in the Commonwealth of Pennsylvania are suspected as being the norm for others who experience a lower risk of seismic activity than California. - Reproduced
Keywords: Earthquake prediction